MODEL PENANAMAN AKHLAK BERBASIS BUDAYA MEMBACA AL-QUR’AN (STUDI KASUS DI SDIT AS-ASYAFI’IYAH KENDAL BLEMBEM JAMBON PONOROGO) - Anis Mubarok Habibulloh; Rido Kurnianto; Nurul Abidin (Universitas Muhammadiyah Ponorogo, 2018)
SDIT As-Syafi’iyah Kendal Blembem Jambon Ponorogo is one of the educational institutions that implements the importance of moral cultivation in the education process. This Integrated Islamic Primary School has applied the culture of reading Al- Qur’an sincc its inccption. To overcome the problem of morals in students. SDIT As-Syafi’iyah Kendal Blembem Jambon Ponorogo is doing moral cultivation through the culture of reading the Qur’an before the teaching and learning activities begin. This research was conducted with the aim of: To find out the application of students’ Al-Qur’an reading culture at SDIT As-Syafi’iyah Kendal Blembem Jambon Ponorogo, a moral-based cultivation model of student reading Al-Qur’an, inhibiting factors and supporting moral-based planting models the culture of reading the Qur’an. This research uses qualitative descriptive research, and the data collection is done by interviewing, observing, and documenting methods, all of which are used for the Moral Cultivation Model Based on the Culture of Reading Al- Qur’an. The results of this study are summarized as follows: (1) the application of the Al-Qur’an reading culture at SDIT As-Syafi’iyah is carried out every day at 06.30 a.m. to 07.00 a.m. before the Bina Nafsiyah is carried out and the class hours begin. Whereas the implementation of the method or the method of applying the culture of reading Al-Qur’an in SDIT As-Syafi’iyah with the sorogan system is that student read the Qur’an in a way one by one directly facing the teacher. The culture of reading Al-Qur’an can shape children to be children of good character, good character, courteous and polite, and to be pious children. (2) A model of cultural-based moral cultivation reads the Holy Al-Qur’an at SDIT As-Syafi’iyah Kendal Blembem Jambon Ponorogo through: Worship, prohibition or order (Amar Ma’ruf Nahi Munkar), giving advice, and setting an example. (3) Factors supporting the moral cultivation model based on the culture of reading Al-Qur’an at SDIT As-Syafi’iyah, namely: mentoring, religious support activities and adequate facilities and infrastructure. While the inhibiting factor is student guardians who are less cooperative with the school, there are technological advances that interfere with the learning process of student.